Obstacles, Realities and Opportunities in Human Resources Management in Public Administration Institutions From Bihor County (Romania) and Hajdú-Bihar County (Hungary) - Maria-Madela ABRUDAN; Tomina Gabriela SĂVEANU; Mirabela MATEI; Mária UJHELYI (Transylvanian Review of Administrative Sciences, 2015)
The aim of this paper is to analyze the par-ticularities of human resources management in the public institutions from Bihor County (Ro-mania) and Hajdu-Bihar County (Hungary). The comparative dimension of our study is framed in Hofstede’s categories of cultural differences in organizational culture. The data presented is derived from a broader study conducted on the implementation of New Public Management at local public administration institutions in Ro-mania and Hungary. The project entitled ‘Es-tablishment of R&D programmes in the f eld of new public management between economic faculties of higher education in Hajdu-Bihar and Bihor Counties’ (HURO/0901/277/2.2.2) was developed in partnership between Faculties of Economics from the Universities of Oradea and Debrecen. Our results on public human resour-ces provide relevant insight in the processes re-garding personnel in the public institutions in this region and propose solutions for improvement of the observed weaknesses. The employees of the 60 public institutions included in this research consider themselves participants in the decision-al process, yet the evaluation process needs to be reshaped in order to provide a better balance between performances and the rewards system.